The pH variation of microbial suspension after gas bubbling and sonication - Koval, Iryna (Видавництво Львівської політехніки, 2013)
It was described the influence of pH reduction on the water disinfection processes. Ultrasonic role on the pH change in the atmosphere of carbon dioxide, oxygen, argon and helium was explained in the given work. It was establishment that bubbling of carbon dioxide in the present of US action has no provided to the rapid decrease of pH value in suspension compared with CO2 alone. The results obtained support a promising future for the application of sonochemistry in water treatment.
Keywords: pH value; ultrasound and gas action